A new type of ward for perioperative care in visceral surgery: initial experience in a high-volume center - Siegel, Niels Wolfgang; Hampel, Christopher; Trierweiler-Hauke, Birgit; Weigand, Markus A.; Michalski, Christoph; Nienhüser, Henrik; Mieth, Markus (Deutsches Ärzteblatt, 2025)
Perioperative care in visceral surgery places considerable demands on intensive care resources (1). Capacity shortages on intensive care units, which are often crucial for postoperative care when there is a significant risk of complications (2), lead to delays in planned surgeries and, particularly for patients with oncological diseases, represent a considerable psychological and prognostic burden (3). Up to now, intermediate care units (IMC) have been established as a transitional level to provide adequate care to patients with limited intensive care requirements. An IMC of this kind has been in place at the surgical center of the Heidelberg University Hospital, Germany, since 2004. There, patients are closely monitored and can receive non-invasive ventilation and catecholamines if necessary. Nevertheless, transfer from intensive care (ICU or IMC) to a general ward remains a critical juncture, since premature transfer may be associated with increased mortality (4). In order to minimize this risk and enable a more targeted use of resources, an advanced care unit (ACU) was created at Heidelberg University Hospital to provide an additional level of care between the IMC and the general ward.
Gesehen am 22.01.2026